2013
DOI: 10.1111/jgs.12522
|View full text |Cite
|
Sign up to set email alerts
|

Educational Interventions to Improve Recognition of Delirium: A Systematic Review

Abstract: Delirium is a common and serious condition that is underrecognized in older adults in a variety of healthcare settings. It is poorly recognized because of deficiencies in provider knowledge and its atypical presentation. Early recognition of delirium is warranted to better manage the disease and prevent the adverse outcomes associated with it. The purpose of this article is to review the literature concerning educational interventions focusing on recognition of delirium. The Medline and Cumulative Index to Nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 38 publications
1
70
0
1
Order By: Relevance
“…The results of this study showed three outcomes supporting this idea. ( Donahue, Kazer, Smith, & Fitzpatrick, 2011;Vargheseet al,2014;Yanamadala, Wieland, & Heflin, 2013) showed that educational programs and bedside coaching ( El Hussein, Hirst, &Salyers, 2015) were effective in increasing knowledge, and producing positive changes in staff behaviors, practices and participant outcomes. These educational programs included information about the eight topics mentioned above regarding delirium and the screening instruments.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed three outcomes supporting this idea. ( Donahue, Kazer, Smith, & Fitzpatrick, 2011;Vargheseet al,2014;Yanamadala, Wieland, & Heflin, 2013) showed that educational programs and bedside coaching ( El Hussein, Hirst, &Salyers, 2015) were effective in increasing knowledge, and producing positive changes in staff behaviors, practices and participant outcomes. These educational programs included information about the eight topics mentioned above regarding delirium and the screening instruments.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Davis and MacLullich (2009), 86% respondents were aware that acute onset was an essential criterion for delirium and almost all agreed that doctors working in acute medical settings should have a good working knowledge of delirium. Importantly, findings of a recent systematic review failed to show that improvement in skills and knowledge alone had a favorable influence on the recognition of delirium (Yanamadala et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While, changes to healthcare systems that facilitate the assessment and management of the elderly are important, we believe that deeper thinking into the nature of medical and nursing training is necessary for finding solutions for improved healthcare for the geriatric population. Yanamadala et al (2013) used the Predisposing, Reinforcing, and Enabling Constructs in Educational Diagnosis and Evaluation (PRECEDE) model in their systematic review. They classified educational interventions into four types depending on the nature of the intervention, i.e., whether they were didactic; whether they facilitated change in performance by providing; reinforced learning through reminders and feedback or; were a combination of all three.…”
Section: Looking Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…As recommended by AGS, multiple non-pharmacological interventions have been used to prevent and treat delirium including behavioral interventions, rehabilitation, environmental adaptation, psychological and social supports, medication reductions and system and process changes (60). Several programs including various nonpharmacological interventions have been studied (61,62).…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%